Urothelkarzinom des oberen und unteren Harntrakts - welche Risikofaktoren machen Früherkennungsmaßnahmen sinnvoll?: Leitthema - Westhoff, Niklas Christian; Rieger, Constantin; Heidenreich, Axel; Bolenz, Christian; Michel, Maurice Stephan (Die Urologie, 2025)
Urothelial carcinoma is one of the most common malignancies both in Germany and worldwide. Due to the frequent occurrence of late-onset or nonspecific symptoms, carcinomas are often diagnosed at advanced stages. Structured early detection programs have the potential to detect urothelial carcinoma in earlier stages and to improve survival rates. Various risk factors are associated with urothelial carcinoma, most notably tobacco abuse and occupational exposure, as well as genetic disorders such as Lynch syndrome in upper urinary tract carcinoma. In clinical practice, diagnostic tools include general examinations and ultrasound imaging of the urinary tract, with microhematuria and urine cytology playing key roles. For screening purposes noninvasive urine markers have demonstrated limited evidence. Despite the lack of optimal diagnostic markers for systematic early detection in high-risk populations, it is essential to ensure that every patient presenting with hematuria undergoes appropriate and risk-adapted diagnostics.
Online publiziert: 26. November 2024
Gesehen am 01.04.2025